Were anxiety, depression and psychological distress associated with local mortality rates during COVID-19 outbreak in Italy? Findings from the COMET study. (August 2022) - Carrà, Giuseppe; Crocamo, Cristina; Bartoli, Francesco; Riboldi, Ilaria; Sampogna, Gaia; Luciano, Mario; Albert, Umberto; Carmassi, Claudia; Cirulli, Francesca; Dell'Osso, Bernardo; Menculini, Giulia; Nanni, Maria Giulia; et al.
Abstract: Background: The mental health of the Italian population declined at the onset of the COVID-19 pandemic. However, nationwide population prevalence estimates may not effectively reproduce the heterogeneity in distress responses to the pandemic. In particular, contextual determinants specific to COVID-19 pandemic need to be considered. We thus aimed to explore the association between local COVID-19 mortality rates and mental health response among the general population. Methods: We capitalised on data (N = 17, 628) from a large, cross-sectional, national survey, the COMET study, run between March and May 2020. While psychological distress was measured by General Health Questionnaire–12 (GHQ-12), the Depression, Anxiety and Stress Scale-21 Items (DASS-21) was used to assess relevant domains. In addition, a Covid-19 mortality ratio was built to compare single regional mortality rates to the national estimate and official statistics were used to control for other area-level determinants. Results: Adjusted ordered regression analyses showed an association between mortality ratio and moderate (OR = 1.10, 95%CI 1.03–1.18) and severe (OR = 1.11, 95%CI 1.03–1.21) DASS-21 anxiety levels. No effects of mortality ratio on GHQ-12 scores and DASS-21 depression and stress levels, uniformly high across the country, were estimated. Conclusions: Although we could not find any association between regional COVID-19 mortality ratio and depression or psychological distress, anxiety levels were significantly increased among subjects from areas with the highest mortality rates. Local mortality rate seems a meaningful driver for anxiety among the general population. Considering the potentially long-lasting scenario, local public health authorities should provide neighbouring communities with preventive interventions reducing psychological isolation and anxiety levels. Highlights: Contextual factors related to COVID-19 might produce different distress responses. We uncovered an association between local COVID-19 mortality rates and anxiety. No association with depression or psychological distress was estimated.